2017
DOI: 10.1080/13603116.2017.1335355
|View full text |Cite
|
Sign up to set email alerts
|

Piloting autism intervention research with teachers in mainstream classrooms

Abstract: Although there is a recognised need for effective practices to support students on the autism spectrum in mainstream schools, there is a research to practice gap in the area of autism and education, whereby evidence-based intervention may take decades to translate into mainstream classroom practice. Thus, current recommendations are that, rather than presenting mainstream school teachers with interventions developed and tested in clinical or special education settings, a participatory research process should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The results showed that the use of WDA (Wacker Daily Activity) media was able to improve the ability to understand the schedule of daily activities in children with autism. These data reinforce the findings which informed that when parents and teachers find ways or media to intervene children with autism than the children can be assisted in understanding the daily activity [11].…”
Section: Baseline Data 2 (A2)supporting
confidence: 84%
“…The results showed that the use of WDA (Wacker Daily Activity) media was able to improve the ability to understand the schedule of daily activities in children with autism. These data reinforce the findings which informed that when parents and teachers find ways or media to intervene children with autism than the children can be assisted in understanding the daily activity [11].…”
Section: Baseline Data 2 (A2)supporting
confidence: 84%
“…Macdonald et al (2017) claim that there is an urgent need for interventions to develop results that support autistic students in general education. They studied the implementation of an intervention model and conducted collaborative research (2017). Stokes et al (2017) also focused on didactic strategies in the classroom.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were found with a didactical perspective, and by that, we identified a lack of studies that focuses on the didactical aspects of inclusive education. However, Macdonald et al (2017) is an exception; their study of how to enhance the degree of knowledge development in students is important for raising the future knowledge development for autistic students in general classrooms. And as mentioned before, there is also a limited amount of studies (6) that address the role of sensory challenges in creating inclusive learning environments for autistic students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of our study is to delve into the attitudes of teachers towards the inclusion of learners with ASD and examine the impact of these attitudes on their general perceptions of inclusive education. Given the relevance of such attitudes and their impact on teaching practices, and considering the small number of studies focused on this subject with specific regard to learners with ASD (Cassimos et al, 2015; Macdonald et al, 2017), it is necessary to carry out more studies in this area, with the aim of defining the factors that influence these attitudes, related both to the teachers themselves and to the context.…”
Section: Introductionmentioning
confidence: 99%